SysML for systems engineering : a model-based approach - Holt, Jon; Perry, Simon (Professional applications of computing series ;, 2018)
In this Book the following topics are covered: Model-based Systems Engineering; Domain-specific languages; MBSE Ontologies ; Systems Modelling; SysML; Requirements Modelling; Process Modelling ;and Value Chain modelling.